(untitled) (Praxis Educativa, 2016)
Since the end of World War II, the pillars of modern life narratives started to be questioned, including those relating to the ideas of progress and/ or the promises of better futures and the role of education (Adorno, 1967). In this context, the processes of crisis and transformation of capitalist societies involved the working world, the nation- state configurations as educational systems that were set up around that promises of progress. Likewise, the reform processes of education settled down on these narratives emphasizing the school´s secondary character as an area of socialization in contemporary societies. Within this framework of discussion, this article intends to discuss, to put pressure on the discourses about young people, their schools and neighborhoods, especially for those living in contexts of extreme urban poverty, recovering their voices, what they say about their education, their future, their desires and fears.